AUTENTIKASI MINYAK BUAH MERAH DALAM CAMPURAN MINYAK KEDELAI DAN MINYAK JAGUNG DENGAN METODE SPEKTROFOTOMETRI INFRAMERAH YANG DIKOMBINASIKAN DENGAN KEMOMETRIKA - , DWI LARASATI SETYANINGRUM, Prof. Dr. Sugeng Riyanto M.S., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Red Fruit (Pandanus conoideus Lam) is typical plant or endemic which grow at Papua Island. Red fruit oil (RFO) can be considered as functional food oil because not only served as a diet but also as preventive agents of various diseases. Authentication of red fruit oil (RFO) becomes very important since the price of RFO is 10-15 times higher than that of common vegetable oils. The oil can be easily faked with other cheaper oils such as corn oil and soybean oil. Combinations of Fourier Transform Infrared (FTIR) spectroscopy with chemometrics have been developed to detect and quantify the existed adulteration on red fruit oil. RFO was prepared in binary mixture with corn oil (CO) and soybean oil (SO) and were quantitatively analyzed using FTIR spectroscopy with ATR sampling handling. Multivariate calibration method, principal component analysis (PCA), partial least square (PLS) and principle component regression (PCR), was used to construct the calibration model at different frequencies that differentiate RFO from corn oil and soybean oil. Based on the highest values of coefficients of determination (R2) and the lowest values of root mean standard error of calibration (RMSEC), PLS with normal FTIR spectra at frequency region of 1800-1600 cm-1 was selected for authentication of RFO in binary mixture with corn oil with R2 of 0,9976 and RMSEC of 0,9745. Normal FTIR spectra at frequency region of 4000-650 cm-1 with R2 of 0,9993 and RMSEC of 0,8232 was selected for authentication of RFO in binary mixture with soybean oil. Meanwhile, PLS with normal FTIR spectra at frequency region of 1200-900